Common Management Issues in Pediatric Patients with Mild Bleeding Disorders - O'Brien, Sarah H. (Seminars in Thrombosis and Hemostasis, 2012)
Type 1 von Willebrand disease and mild platelet function defects are among the most common disorders seen by pediatric hematologists. The management and prevention of bleeding in these patients can be challenging, as there are limited published data to guide clinical practice, and a complete lack of randomized clinical trials. Desmopressin (DDAVP) and antifibrinolytics are the mainstays of treatment in these patients, yet the optimal dosing and timing of these agents to prevent or resolve bleeding, while minimizing adverse side effects, is sometimes unclear. DDAVP-induced hyponatremia is a particularly under-recognized complication in children with bleeding disorders who undergo surgery. Clinicians need to be aware of local measures that are equally important in treating problems such as epistaxis and surgical bleeding. This review will discuss the published literature and provide practical suggestions regarding four common management issues in the care of children and adolescents with mild bleeding disorders: epistaxis, heavy menstrual bleeding, dental extractions, and tonsillectomy.
Keywords: epistaxis; menorrhagia; tonsillectomy; dental extraction; von Willebrand disease